Energy Analysis on Dynamic Fragmentation Degree of Cemented Sand Specimens under Confining Pressure - Ying Xu; Jinjin Ge; Wei Huang (Shock and Vibration)
In order to study the fragmentation energy dissipation characteristics of cemented sand specimens under confining pressure and impact loads, the energy consumption of cemented sand specimens was analyzed through an impact compression and split test performed at different loading rates with different impact pressures by using a variable cross section SHPB (split Hopkinson pressure bar) with an active confining pressure loading apparatus. The results show that (1) the absorbed energy and incident energy were in a linear relationship and the proportion between them was relatively constant under confining pressure, and the absorbed energy had a quadratic relationship with the incident energy under zero confining pressure. (2) The fracture energy ratio increased with the increase in incident energy, the damage energy ratio decreased with the increase in incident energy, and the damage energy ratio were always higher than the fracture energy ratio under confining pressure. (3) The energy absorbed by the cemented sand specimens decreased sharply with the increase of confining pressure under the same incident wave energy conditions, and the reflected wave energy and transmitted wave energy increased. (4) When the incident wave energy was constant, the ratio of the energy causing surface fractures to the energy absorbed by the cemented sand specimens decreased sharply with the increase of confining pressure, while the energy causing crack growth and damage increased sharply. These conclusions may guide similar models of blasting tests in the future.